Improving Student Learning Outcomes by Using the PJBL Model Assisted by the EDU Assemblr Application Media - Wulan Nawangsari; Hari Sunaryo; Lia Angela Rosalia (Universitas Muhammadiyah Enrekang, 2023)
This study aims to improve student learning outcomes in the water cycle material with the Project Based Learning learning model assisted by the Assemblr EDU application media, describing the increase in student learning outcomes in the water cycle material after creating an Augmented Realty project assisted by the Assemblr EDU application media. The research conducted was a class action research that had been carried out in 2 cycles. The research subjects were fifth grade students at SDN 2 Mungkung Rejoso, a total of 15 students in the even semester of the 2022/2023 academic year. The research results obtained showed that there was an increase in student learning outcomes after applying the Project Based Learning learning model with the help of the Assemblr EDU application media. Keywords: improvement, PJBL learning, Assemblr EDU, Augmented Realty.